Shredded Catfish (Pangasius hypophthalmus) as a Source of Protein in Balado Seasoning (JURNAL PROTEKSI KESEHATAN, 2022)
Protein is the most important nutrient for our body, because as a source of energy, protein alsoas a body-building substance, a regulatory substance in the body. In addition to building blocks, its main function for the body is to form new tissues (for example forming a fetus during a mother's pregnancy or new tissues during a child's growth process), as well as maintaining existing tissues or replacing parts that have been damaged. Balado seasoning is a food additive that is used as a flavoring to improve the taste of snacks, and shredded catfish is processed from catfish that contains protein so that it can be a source of protein for the body. The purpose of this study was to determine the protein content in balado seasoning with the addition of shredded catfish. Quantitative assay of protein was carried out by the Kjeldahl method, with three stages, namely destruction, distillation and titration. The samples used were samples of balado seasoning and shredded catfish. Balado seasoning does not contain protein as stated on the packaging. In this study, it was found that the protein content of the balado seasoning sample added with shredded catfish was 21,90% and the shredded catfish itself had a protein content of 33,89%. The results obtained in the analysis of protein levels in the balado seasoning after the addition of catfish shredded were higher than the balado seasoning without the addition of catfish shredded before processing.